2004
DOI: 10.3200/jexe.72.4.331-346
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics and Science Self-Concept: An International Investigation

Abstract: Using data from different countries, the author conducted an international investigation of the relationship between mean country mathematics and science self-concept and respective mean country achievement and geographic region. In addition, the relationship between self-concept and gender and age was compared for the different countries. Findings showed, at the student level, an overall positive relationship between achievement and self-concept in the countries investigated. However, at the country level, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
141
2
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(170 citation statements)
references
References 23 publications
17
141
2
10
Order By: Relevance
“…Başarı algısı, öğrencinin okulla ilişkili öz-benliğinin anahtar bileşenidir (Bong ve Skaalvik, 2003). Başarı ile matematik ve fen bilgisi öz-benliği arasında pozitif ilişki olduğunu çeşitli çalışmalar göstermiştir (Chiu ve Xihua, 2008;Liu ve Meng, 2010;Wilkins, 2004;Yoshino, 2012;Shen ve Pedulla, 2000). Akademik öz-benliğin ilgiyi etkilediği gösterilmesine karşın (Krapp 2000;Köller, Baumert ve Schnabel, 2001), ilginin öz-benlik üzerindeki etkisi oldukça azdır (Marsh, Trautwein, Lüdtke, Köller, ve Baumert, 2005).…”
unclassified
“…Başarı algısı, öğrencinin okulla ilişkili öz-benliğinin anahtar bileşenidir (Bong ve Skaalvik, 2003). Başarı ile matematik ve fen bilgisi öz-benliği arasında pozitif ilişki olduğunu çeşitli çalışmalar göstermiştir (Chiu ve Xihua, 2008;Liu ve Meng, 2010;Wilkins, 2004;Yoshino, 2012;Shen ve Pedulla, 2000). Akademik öz-benliğin ilgiyi etkilediği gösterilmesine karşın (Krapp 2000;Köller, Baumert ve Schnabel, 2001), ilginin öz-benlik üzerindeki etkisi oldukça azdır (Marsh, Trautwein, Lüdtke, Köller, ve Baumert, 2005).…”
unclassified
“…This result was also obtained at the international level by Wilkins, Zembylas, and Travers (2002) in their study reviewing TIMSS data for16 countries and by Wilkins (2004) in his study reviewing TIMSS data for 41 countries and 290,000 students. In a similar study, Rinn, McQueen, Clark, and Rumsey (2008) found a positive relationship between mathematics achievement and mathematics self-concept among 181 gifted students.…”
Section: Academic Self-conceptmentioning
confidence: 58%
“…Academic self-concept includes a comparison in competence from one subject domain to another (i.e., from reading to mathematics) and from one student to another (Cokley, 2000;Marsh, 1990;Rinn, McQueen, Clark, & Rumsey, 2008). In general, researchers report that students' in elementary school exhibit a stronger self-concept than those in high school (Linver & Davis-Kean, 2005;Wilkins, 2004;Wilkins & Ma, 2003).…”
Section: Academic Self-conceptmentioning
confidence: 99%
See 2 more Smart Citations